2019
DOI: 10.1038/s41598-019-55345-x
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size Requirements of Glaucoma Clinical Trials When Using Combined Optical Coherence Tomography and Visual Field Endpoints

Abstract: Glaucoma clinical trials using visual field (VF) endpoints currently require large sample sizes because of the slowly-progressive nature of this disease. We sought to examine whether the combined use of VF testing and non-invasive optical coherence tomography (OCT) imaging of the neuroretinal tissue could improve the feasibility of such trials. To examine this, we included 192 eyes of 121 glaucoma participants seen at ≥5 visits over a 2-year period to extract real-world estimates of the rates of change and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…26 To date, studies suggesting the usefulness of this approach, which recommends intense testing at the beginning and end of follow-up, have been limited to computerized simulations or longer periods of follow-up than the present investigation. 40,41 In the UKGTS, 5 clustering was performed at baseline, 18 months, and 24 months. The investigators were able to detect statistically significant changes even at 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…26 To date, studies suggesting the usefulness of this approach, which recommends intense testing at the beginning and end of follow-up, have been limited to computerized simulations or longer periods of follow-up than the present investigation. 40,41 In the UKGTS, 5 clustering was performed at baseline, 18 months, and 24 months. The investigators were able to detect statistically significant changes even at 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of using MD slopes for reducing the sample size requirements in glaucoma trials have been recently discussed. [15][16][17][18][19] Wu at al. have shown that the feasibility of glaucoma clinical trials could be improved by evaluating differences in the rate of visual eld change (slopes) between randomization groups.…”
Section: Discussionmentioning
confidence: 99%
“…Per the committee's discussion, an alternative glaucoma endpoint for pivotal trials should have a strong correlation and predictability of either current or future visual function, such as that measured with the above cited acceptable endpoints. 12 Investigators have reported the advantages of using visual eld mean deviation (MD) slopes as an endpoint in glaucoma clinical trials because studies employing trend analysis of visual eld global indices would likely require a smaller sample size than event-based endpoints, [15][16][17][18][19] such as the ones currently acceptable by the FDA. The purpose of the present study is to evaluate the relationship between MD slope from visual eld tests collected over a short period of time (2 years) and the current FDA recommended endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…In glaucoma clinical research, not only the slow progression of the disease but also the considerable noise in perimetry-based functional endpoints historically necessitated very large sample sizes [ 40 ]. Adding a structural dimension to a functional endpoint has shown to improve predictive accuracy for short-term data, increase the statistical power of tests, and therefore allow for reduced sample sizes in clinical trials [ 41 , 42 ]. We will explore combined functional and structural endpoints in iAMD following this prescription from glaucoma clinical research.…”
Section: Discussionmentioning
confidence: 99%